Integration between Surface Geoelectrical and Geotechnical Datasets in Salah Al-DinArea, Central Iraq - Hussein H. Karim; T. Schanz; Ali N. Ibrahim (Engineering and Technology Journal, 2013)
This research aims to assess some geotechnical properties and aquifer parameters and consequently the applicability of predicting its properties from surface electrical resistivity. The main output is to get several geotechnical properties particularly those concerned with groundwater studies (such as porosity, and permeability) and aquifer properties (such as resistivity, hydraulic conductivity and transmissivity). To achieve this goal, interpretations of 50 Schlumberger VES points distributed along 5 profiles, located in Salah Al-Din Governorate in central Iraq, have been carried out. Sounding curve types obtained in the area are mostly QQ and HK types. The application of VES technique has provided detailed information on the thickness and hydrogeoelectrical characteristics of the aquifers in the study area. Based on VES interpretation and their correlation with available geotechnical data, four geoelectric layers were identified; these are topsoil, unsaturated zone, saturated zone and the conductive layer. In addition, two aquifers have been identified in the area under study. The upper is unconfined appeared mainly in eastern side of Tigris River, whereas the lower is semiconfined-confined appeared mainly in the western side of the River. Different target zones for groundwater potential have been recognized on the basis of geoelectric parameters that range between poor-good groundwater potential. Generally, the quality of ground water is considered to be brackish with respect to their total dissolved solids (TDS). Several discontinuities (probably faults) have been delineated according to the form of resistivity curves and geoelectrical sections. The study states that the resistivity values increase with increasing gypsum content in dry condition. But for saturated soil with high water content, the conductivity increases and hence the resistivity decreases. Besides, the increase in gypsum content leads to increase the porosity, then the resistivity increases too. A remarkable correlation is found among topsoil gypsum content, surface resistivity and porosity with Landsat image.